PENGUJIAN STABILITAS SEDIAAN LUKA BAKAR BERBAHAN BAKU AKTIF KITOSAN/EKSTRAK PEGAGAN(CENTELLA ASIATICA) - Eriawan Rismana; Idah Rosidah; Olivia Bunga; Prasetyawan Yunianto; Erna Erna (Jurnal Kimia Terapan Indonesia, 2015)
The evaluation of wound-healing formula stability with active substance chitosan/Centella asiatica extract has been examined. The stability test was evaluated including physical, chemical and microbiology properties. The stability of physical property was observed by organoleptic parameters such as shape of gel, color, odor, homogeneity and weight of samples, while the stability of chemical property was studied by determination of pH and HPLC chromatogram profile. Meanwhile the stability of microbiology property was determined by contents by microbe and fungi contaminant. The results of evaluation showed that the wound-healing formula had a good stability for all properties after storage at room temperature for 24 weeks and 40 oC/75 % RH for 12 weeks.Keywords: Wound-healing formula, chitosan, Centella asiatica extract, evaluation, stability